Role of the digital for the Third Sector in the Campania region (Italy): From the side of research to the side of the objects in the aftermath of the COVID-19 pandemic - Punziano, Gabriella; Cicellin, Mariavittoria; Zito, Eugenio; Acampa, Suania; Sorrentino, Rosa (Italian Sociological Review, 2023)
This paper aims to investigate the role of the digital in facing the social and practical impact of the Covid-19 pandemic on particularly fragile and affected realities, Third Sector Organizations (TSO), in a context pervaded by structural and socio-economic weaknesses, the Campania Region in south Italy. It analyzes the digital object as: 1. a process - digitization/digitalization and digital transformation, 2. as a scenario - in which identities, activities, and alternative spaces of use or data collection transit and are constructed, and as 3. skills and capabilities - as social capital and value. This re-framing work is intended to be a useful tool for reflecting on the role of digital in research processes, while also offering a contribution to the debate on the Third Sector in contexts of crisis, such as the one generated by the COVID-19 pandemic, that impact its existence, activity, shape, and perspectives.